Circadian Rhythmic Characteristics in Men With Substance Use Disorder Under Treatment. Influence of Age of Onset of Substance Use and Duration of Abstinence - Capella, Maria del Mar; Martinez-Nicolas, Antonio; Adan, Ana (Frontiers in Psychiatry, 2018)
There is evidence of the reciprocal influence between the alteration of circadian rhythms and Substance Use Disorders (SUD), and part of the success of the SUD treatment lays in the patient’s rhythmic recovery. We aim to elucidate the effect of the SUD treatment in circadian rhythmicity considering, for the first time, the age of onset of substance use (OSU) and duration of abstinence. We registered the sleep-wake schedules, the chronotype and the distal skin temperature of 114 SUD patients with at least 3 months of abstinence, considering whether they had begun consumption at age 16 or earlier (OSU≤16, n = 56) or at 17 or later (OSU≥17, n = 58), and duration of abstinence as short (SA: three to five months, n = 38), medium (MA: six to nine months, n = 35) or long (LA: more than nine months, n = 41). Moreover, we compared the patients’ distal skin temperature pattern with a similar sample of healthy controls (HC, n = 103). SUD patients showed a morningness tendency and higher night values, amplitude and stability, a better adjustment to the cosine model and lower minimum temperature and circadianity index in the distal skin temperature rhythm, in contrast to the HC group. The OSU≥17 and LA groups showed a more robust distal skin temperature pattern, as well as milder clinical characteristics when compared to the OSU≤16 and SA groups, respectively. The circadian disturbances associated to substance consumption seem to improve with treatment, although the age of OSU and the duration of abstinence are modulating variables. Our results highlight the need to include chronobiological strategies that boost circadian rhythmicity both in SUD prevention and rehabilitation programs. The measurement of distal skin temperature rhythm, a simple and reliable procedure, could be considered an indicator of response to treatment in SUD patients.